Validasi Metode Identifikasi Sildenafil Sitrat, Tadalafil dan Fenilbutazon dalam Jamu Obat Kuat Secara Kromatografi Lapis Tipis – Densitometri - Setiawan, Henry Kurnia; Kahar, Neysa Marcella; Stephanie, Stephanie; Sukarti, Emi (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2020)
Jamu/Herbal Medicine that contain chemical compounds/Pharmaceutical compounds has been banned by The National Agency of Drug and Food Control in Indonesia, but in December 2017, BPOM released a public warning about aphrodisiac herbal medicine that contain chemical compound like sildenafil citrate and phenylbutazone in the market. The aim of this study was to find out the valid method for identification of sildenafil citrate and phenylbutazone in aphrodisiac herbal medicine. In this study, the developed method was applied to 22 brands of aphrodisiac herbal medicine sample. Sample was extracted with methanol, then 5 µl of sample spotted on silica gel plate 60 F 254 and eluated by chloroform : methanol : amonia (70 : 3 : 1.5, v/v/v). The spots were analyzed by TLC scanner at λ 286 nm. Sildenafil citrate was appeared at Rf 0.76; tadalafil at 0.6 and phenylbutazone at Rf 0.12 with resolution (Rs) value of sildenafil and tadalafil was 1.1 meanwhile tadalafil and phenylbutazone was 5.4. Limit of detection of sildenafil citrate was 8.552 µg/ml (2.053 mg/600 mg capsul), tadalafil was 1.629 µg/ml (0.391 mg/600 mg capsul), and phenylbutazone was 7.877 µg/ml (1.890 mg/600 mg capsul). This study found 14 brands that gave a positive result containing sildenafil citrate and no sample contain tadalafil and phenylbutazone.